SMEs High-Growth in Thailand - Rojsurakitti, Terdsak (Archives of Business Research, 2015)
SMEs High-Growth in Thailand Abstract This study investigated in the secondary data regards to SMEs High growth sectors of Hong Kong, Japan and Hungary. The result found that these 3 countries have been promoting SME sectors under the differentiation in structures and economics, so that, this study attempt to identify Key Performance Indicators (KPIs) and classified SME High Growth Sector in Thailand which are (1)Economic Growth (2) Value Added (3) Employment (4) Technological Intensiveness. The study also examined Policies that connected with the promotion of High Growth SMEs in Hong Kong, Japan and Hungary which based on Market Failure Theory and State Failure Theory. From analysis, Key Performance Indicators of SME high growth sectors in Thailand are (1) Food industry (2) Textile industry (3) Machinery industry (4) Rubber industry and products (5) Gems and jewelry industry (6) Plastics and packaging industry. Thus, Thai government should adopt successful schemes from best practices in order to expand Thai economic into ASEAN and global market. Keywords: SMEs, Performance Indicators (KPIs), classified SME High Growth Sector, Economic Growth, Value Added, Employment, Technological Intensiveness